Emocja strachu jako jeden ze środków manipulacji językowej (na przykładzie tekstów współczesnej prasy rosyjskiej) - Małecki, Łukasz (Studia Rossica Posnaniensia, 2010)
Changes in political and social life, determined by the influence of mass-media, create a large space for manipulation. The purpose of the paper was to analyze texts that contain and perform persuasive (manipulation) function. The author presents one kind of persuasion which is based on the influence of emotions – first of all the influence of fear. The relation between the emotion of fear and language manipulation has been exemplified on publicistic texts.